Strategy for Development of Cattle Breeding and Reproductive Businesses in the Cikedung People’s Livestock Area - Y. Saputra; R. Priyanto; B. W. Putra; L. Cyrilla (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2025)
Cikedung District, a region with significant livestock potential, has yet to be comprehensively evaluated regarding cattle production and reproductive performance, agricultural waste utilization, cattle population, and rearing pattern diversity (intensive and semi-intensive). This study aims to formulate development strategies for local cattle breeding enterprises in the Cikedung area. Data were collected through observations and analyzed using the SOAR (Strengths, Opportunities, Aspirations, Results) framework and the AHP (Analytical Hierarchy Process). The findings indicate that the development of cattle breeding businesses in Cikedung is influenced by internal factors, including production performance, calf births, and increased availability of green fodder, as well as external factors, such as marketing technology and expanded market access. The priority strategies identified are (1) enhancing sales and marketing, (2) standardizing livestock quality, and (3) strengthening the capacity of livestock farmers to produce higherquality cattle at competitive prices, thereby increasing farmers income. Key recommendations include adopting group-based livestock management approaches, expanding market access, optimizing the use of livestock resources, and fostering collaborations with government entities and stakeholders to advance cattle breeding initiatives in Cikedung.